The Effect of Collaborative Learning Models, Independent Learning, and Self-Confidence on IPAS Problem-Solving Skills - Agus Riyadi; Dian Septi Nur; M. Abdul Roziq Asrori (Salus Publica: Journal of Community Service, 2026)
This study aims to analyse the effect of collaborative learning models, independent learning, and self-confidence on the problem-solving abilities of IPAS students at Pakel 2 Public Elementary School. Using an ex post facto quantitative approach, the research sample consisted of 52 students. Data analysis was conducted using multiple linear regression. The results showed that simultaneously, the three independent variables had a significant effect on problem-solving skills with a contribution (R2) of 83.4%. Partially, the collaborative learning model was the strongest predictor. These findings indicate the need to integrate collaborative strategies supported by strengthening students' internal character.